The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0003319714544355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Residing Altitude on Levels of High-Density Lipoprotein Cholesterol

Abstract: Lower mortality rates from coronary heart disease and higher levels of serum high-density lipoprotein cholesterol (HDL-C) have been observed in populations residing at high altitude. However, this effect has not been investigated in Arab populations, which exhibit considerable genetic homogeneity. We assessed the relationship between residing altitude and HDL-C in 2 genetically similar Omani Arab populations residing at different altitudes. The association between the levels of HDL-C and other metabolic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…Living at high altitude areas requires physiological adaptations, which in turn may provide additional avenues for explanations. Literature reports that higher HDL-c levels have been observed in high altitude compared to low-altitude groups, but this is contradictory to our findings [43] .…”
Section: Discussioncontrasting
confidence: 99%
“…Living at high altitude areas requires physiological adaptations, which in turn may provide additional avenues for explanations. Literature reports that higher HDL-c levels have been observed in high altitude compared to low-altitude groups, but this is contradictory to our findings [43] .…”
Section: Discussioncontrasting
confidence: 99%
“…7 These studies showed crude estimates and did not adjust by potential confounders nor by BMI, limiting the comparability with our findings. A separate study from Oman, in the Arabian peninsula, compared HDL-c levels in families living at different altitudes, that is, 2000 vs 700 m.a.s.l., and found that this marker was lower in the population living at higher altitude in the order of –0.39 mmol/L (15 mg/dL), 8 a difference that may not have much clinical relevance. In our study, we did not observe an association between low HDL-c and altitude.…”
Section: Discussionmentioning
confidence: 94%
“…relative to those who live at sea level. 8 These studies denote that the controversial results in the association between high altitude and dyslipidemia patterns and does not account for the rural/urban effect that is also be present even at different altitudes.…”
Section: Introductionmentioning
confidence: 94%
“…A cross sectional study from the United States shows that adults living at altitudes of 1500-3500 m are less likely to have diabetes and obesity compared with adults living at elevations of 0-499 m. After adjusting for factors such as age, physical activity, and obesity, the association between diabetes and altitude persisted (Woolcott et al, 2014). In terms of hyperlipidemia, a study of an Omani Arab population residing at high altitude demonstrates elevated high density lipoprotein cholesterol (HDL-C) levels, while a cross-sectional Turkish study shows that dyslipidemia is negatively associated with altitude (Bayram et al, 2014;Al Riyami et al, 2015). This effect is thought to be mediated through HIF1 in reducing cholesterol synthesis by 3-hydroxy-3-methylglutaryl-CoA reductase (Nguyen et al, 2007).…”
Section: Is Residence At Altitude Beneficial?mentioning
confidence: 99%